Allogenic Adipose Tissue-Derived Stromal/Stem Cells and Vitamin D Supplementation in Patients With Recent-Onset Type 1 Diabetes Mellitus: A 3-Month Follow-Up Pilot Study - Araujo, Debora B.; Dantas, Joana R.; Silva, Karina R.; Souto, Débora L.; Pereira, Maria de Fátima C.; Moreira, Jessica P.; Luiz, Ronir R.; Claudio-Da-Silva, Cesar S.; Gabbay, Monica A. L.; Dib, Sergio A.; Couri, Carlos E. B.; Maiolino, Angelo; et al. (Frontiers in Immunology, 2020)
Objective: To evaluate the short term safety and potential therapeutic effect of allogenic adipose tissue-derived stromal/stem cells (ASCs) + cholecalciferol in patients with recent-onset T1D. Methods: Prospective, phase II, open trial, pilot study in which patients with recent onset T1D received ASCs (1 × 106 cells/kg) and cholecalciferol 2000 UI/day for 3 months (group 1) and were compared to controls with standard insulin therapy (group 2). Adverse events, C-peptide (CP), insulin dose, HbA1c, time in range (TIR), glucose variability (continuous glucose monitoring) and frequency of CD4+FoxP3+ T-cells (flow cytometry) were evaluated at baseline (T0) and after 3 months (T3). Results: 13 patients were included (8: group 1; 5: group 2). Their mean age and disease duration were 26.7 ± 6.1 years and 2.9 ± 1.05 months. Adverse events were transient headache (n = 8), mild local reactions (n = 7), tachycardia (n = 4), abdominal cramps (n = 1), thrombophlebitis (n = 4), mild floaters (n = 2), central retinal vein occlusion (n = 1, complete resolution). At T3, group 1 had lower insulin requirement (0.22 ± 0.17 vs. 0.61±0.26IU/Kg; p = 0.01) and HbA1c (6.47 ± 0.86 vs. 7.48 ± 0.52%; p = 0.03) than group 2. In group 1, 2 patients became insulin free (for 4 and 8 weeks) and all were in honeymoon at T3 (vs. none in group 2; p = 0.01). CP variations did not differ between groups (−4.6 ± 29.1% vs. +2.3 ± 59.65%; p = 0.83). Conclusions: Allogenic ASCs + cholecalciferol without immunosuppression was associated with stability of CP and unanticipated mild transient adverse events in patients with recent onset T1D. ClinicalTrials.gov registration: NCT03920397.